Integrated disassembly and reprocessing lot-sizing for multi-level structured products in remanufacturing systems. Issue 9 (2nd September 2022) - Doh, Hyoung-Ho; Lee, Dong-Ho
Abstract : This study addresses a dynamic lot-sizing problem for remanufacturing systems in which end-of-use/life products are disassembled into their parts on a single disassembly workstation and then each part is reprocessed on one of the parallel reprocessing workstations. The problem, which integrates disassembly and reprocessing lot-sizing for multi-level disassembly structures, determines disassembly and reprocessing lot-sizes as well as the workstation on which each part is reprocessed, while satisfying workstation capacities and reprocessed part demands in each period of a planning horizon. An integer programming model is developed that minimizes the sum of set-up, operation and inventory costs. After the NP hardness is shown, two-stage heuristics are proposed in which an initial solution is obtained and then improved by full and partial bi-directional moves. Computational results show that the full move-based heuristic gives near-optimal solutions for small-sized instances and the partial move-based heuristic gives fast solutions with appropriate qualities.